1996
DOI: 10.1111/j.1432-1033.1996.0373k.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Decarboxylase from Pisum sativum

Abstract: To study the molecular structure and function of pyruvate decarboxylase (PDC) from plants the protein was isolated from pea seeds and partially characterised. The active enzyme which occurs in the form of higher oligomers consists of two different subunits appearing in SDSiPAGE and mass spectroscopy experiments. For further experiments, like X-ray crystallography, it was necessary to elucidate the protein sequence.Partial cDNA clones encoding pyruvate decarboxylase from seeds of Pisum sativum cv. Miko have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…As already mentioned, PDCs from plant seeds (e.g., maize, beans, wheat) have generally more complex oligomeric structures. Interestingly though, the values of the kinetic parameters such as substrate affinity, catalytic activity, and reconstitution rate with the cofactors are close to those of the yeast enzyme (10,14,15). Recent studies of enzyme activation and thiol group modifications have, however, revealed significant quantitative differences (10), and the SAXS experiments were aimed at correlating these with possible structural differences.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…As already mentioned, PDCs from plant seeds (e.g., maize, beans, wheat) have generally more complex oligomeric structures. Interestingly though, the values of the kinetic parameters such as substrate affinity, catalytic activity, and reconstitution rate with the cofactors are close to those of the yeast enzyme (10,14,15). Recent studies of enzyme activation and thiol group modifications have, however, revealed significant quantitative differences (10), and the SAXS experiments were aimed at correlating these with possible structural differences.…”
Section: Resultsmentioning
confidence: 87%
“…This enzyme has a lower K M for its substrate pyruvate (0.4 mM (13) compared to 1 mM for the activated state of the yeast and plant enzyme, respectively (9,14)) and higher catalytic activity (180 U/mg compared to 60-80 U/mg for the others). The catalytically active quaternary forms are tetramers in yeast and bacterial PDC and higher oligomers in the enzyme from germinating pea seeds (14) as well as in other plant species (15); however, there is no precise description of the catalytically active states of plant PDCs.…”
mentioning
confidence: 99%
“…4). Biochemical characterizations have demonstrated that, like yeast and some bacterial PDC enzymes, plant PDC has nonlinear kinetics and is activated by its substrate pyruvate (Mü cke et al, 1996;Dietrich and Kö nig, 1997). The PDC2 enzyme, which is constitutively expressed at low levels in roots, is quite different from the anaerobically induced enzyme (R. Dolferus, unpublished data) and may have different kinetic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary transcriptional analysis has revealed that in K. lactis, this regulation occurs at least partly at the level of transcription of the KIPDC1 gene (A. Zeeman, unpublished). Regulation of pyruvate decarboxylase synthesis by oxygen also occurs in plants (Mü cke et al, 1996). In view of its genetic accessibility and the presence of a single structural gene encoding pyruvate decarboxylase (Bianchi et al, 1996), K. lactis is an interesting laboratory system to study regulation of PDC gene expression by oxygen in yeast and to compare this with plant systems.…”
Section: Regulation Of Fermentative Enzymesmentioning
confidence: 99%